Portfolio investment in the twenty first century – a literature review and analysis of flow directions - Broszkiewicz, Magdalena (Economics of the 21st Century, 2017)
The subject of portfolio investment seems particularly significant given that the current fluctuations on international financial markets make it necessary to perform an analysis of their causes and effects. It seems reasonable to make considerations regarding the direction of the flow of portfolio investment in the twentieth and twenty-first century. This article presents theoretical considerations concerning the characteristics and effects of the flow of portfolio investment in the global economy and an analysis of flow directions in the years 1960-2015. These considerations are based on data of the International Monetary Fund and the World Bank, which collate net inflows of the portfolio investment to particular countries in the indicated period. Our considerations show the links between the financial markets of countries and regions, together with the general tendencies of movements of capital at the time of crisis and the stabilization periods of global financial markets. The article shows the link between the financial markets of individual countries, together with the general trend of movement of capital in the period of crisis and the stabilization of financial markets
Ekonomia XXI Wieku = Economics of the 21st Century, 2017, Nr 2, s. 24-38
Keywords: portfolio investment; capital flows; financial crisis; inwestycje portfelowe; przepływy kapitału; kryzysy finansowe